Pengaruh Pemberian Motivasi dan Kompensasi terhadap Peningkatan Produktivitas Kerja Karyawan melalui Penilaian Prestasi pada PT. Lancaster Nusantara Cigarindo Medan - Wahyu Ramadhan; M Ridho Falevi; Yulia Tiara Tanjung (Journal on Education, 2023)
This research aims to determine whether motivation and compensation have a positive and significant effect on increasing work productivity through assessing employee performance at PT. Lancaster Nusantara Cigarindo Medan. The data analysis technique used is a quantitative method with the help of the SPSS program. The sample in this study was 50 respondents. Primary data collection uses a questionnaire. The validity test results for the employee work productivity variable can be declared valid (valid) because all coefficient values are greater than 0.278 R table value. The validity test results for the Compensation variable can be declared valid (valid) because all coefficient values are greater than 0.278 R table value. The validity test results of the work performance assessment variable can be declared valid (valid) because all coefficient values are greater than 0.278 Rtable value. The validity test results of the employee work productivity variable can be declared valid (valid) because all coefficient values are greater than 0.278 Rtable value. The research results show that a). motivation has a positive and significant effect on increasing employee work productivity at PT. Lancaster Nusantara Cigarindo Medan. b). Motivation has a positive and significant effect on employee achievement assessments at PT. Lancester Nusantara Cigarindo Medan. c). Compensation has a positive and significant effect on increasing employee work productivity at PT. Lancaster Nusantara Cigarindo Medan. d). Compensation has a positive and significant effect on employee performance assessments at PT. Lancester Nusantara Cigarindo Medan. e). Achievement appraisals have a positive and significant effect on increasing employee productivity at PT. Lancaster Nusantara Cigarindo Medan. f). Motivation and compensation have a positive and significant effect on increasing work productivity through employee achievement assessments at PT. Lancaster Nusantara Cigarindo Medan.